Mapping Agricultural Constraints: Nationwide Demand-Driven Research, Extension and Policy Perspectives - Singh, Rajbir; Arvind Kumar; ROY, Dr. SURJYA KANTA; Yadav, Preeti; Singh, R. K; Maiti, Sanjit; Burman, R. R (The Indian Journal of Agricultural Sciences, 2026)
Translating farmer knowledge into actionable agricultural policy remains a persistent challenge in agricultural governance. While participatory approaches are widely practiced, large-scale mechanisms for systematically aggregating and validating farmer perceptions remain limited. This study develops and operationalizes a participatory diagnostic framework integrating principles of participatory development and co-production of knowledge to generate structured agricultural policy intelligence. Empirically, the study draws on data generated through the Viksit Krishi Sankalp Abhiyan (VKSA), a nationwide extensive outreach campaign covering a total 11,477 Focus Group Discussions (FGDs) across 448 districts in 34 States and Union Territories (UTs), engaging 1,63,650 farmers, including 55,250 farm women. The FGDs were conducted to identify production constraints across diverse agro-ecological contexts. Farmer-identified issues were consolidated into 20 thematic domains and subsequently validated through severity scoring by Krishi Vigyan Kendra (KVK) scientists using a standardized 10-point scale. Comparative analysis was conducted across four state typologies: large size states, medium size states, small size states/Union territories and North-eastern States. Findings revealed strong convergence across regions around three foundational problems: seed system inefficiencies, climate variability and water management challenges, while also highlighting region-specific priorities related to mechanisation, horticulture systems and integrated crop-livestock production. By aggregating decentralised farmer perceptions into structured severity indices, the study demonstrate how participatory diagnostics can generate decision-oriented agricultural insights. The proposed framework strengthens the Research-Extension-Policy (REP) interface by institutionalising farmer knowledge within scientific validation and policy translation processes. The study contributes both a scalable methodological model and empirical insights that can inform adaptive, regionally differentiated agricultural strategies aimed at enhancing resilience, productivity and sustainability.